The Reliability of Serial Data Communication Using Uart-Usb converter - Cakić, Nikola S; Žigić, Aleksandar; Milosavljević, Srđan (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
During the design of the device that is based on a central microcontroller for measurements and an additional computer for graphical presentation and storage of measurement results, it often happens that there is not enough available USB ports. Therefore the need for using particular serial converters arises. This paper presents the results of reliability testing of serial UART-USB communication using UM232R converter. The development environment Tiva TM4C1294XL microcontroller Launchpad sends temperature measurement results using UART communication to UM232R converter which is connected to ROCK PI 4 single board computer via USB interface. The user application is based on Java programming language and jSerialComm library. The communication is tested using packets of 100, 1 000 i 10 000 arrays of 50 characters. Time intervals used for tests are 10mS, 100mS, 500mS, 1s. Each test is repeated 10 times to improve test validity. The average data loss is 50%, while the proposed algorithm reduced the loss up to 30%.